Biomechanical characterization of human dura mater. (March 2018) - De Kegel, Dries; Vastmans, Julie; Fehervary, Heleen; Depreitere, Bart; Vander Sloten, Jos; Famaey, Nele
Abstract: A reliable computational model of the human head is necessary for better understanding of the physical mechanisms of traumatic brain injury (TBI), car-crash investigation, development of protective head gear and advancement of dural replacement materials. The performance and biofidelity of these models depend largely on the material description of the different structures present in the head. One of these structures is the dura mater, the protective layer around the brain. We tested five human dura mater specimens, with samples at different locations, using planar biaxial tests. We describe the resulting stress-strain curves using both the anisotropic Gasser-Ogden-Holzapfel (GOH) model and the isotropic one-term Ogden model. The low-strain section of the curves is also described using a Neo-Hookean formulation. The obtained stress-strain curves reveal highly nonlinear but isotropic behaviour. A significant amount of inter- and intra-specimen variability is noticed, whereby the latter does not seem to be influenced by location. The GOH model achieves the best fit of the individual test data. A simple Neo-Hookean model can only be used with extreme caution, as it does not manage to capture the nonlinear effects present even at low strains.